The Effects of Concha Bullosa on Lateral Nasal Wall Asymmetries - Mehmet Ekrem Zorlu; Turker Acar; Yakup Sen; Abdulhalim Aysel; Ecem Sevim Akı (European Journal of Rhinology and Allergy)
Objective: The objective is to investigate the efects of unilateral and bilateral concha bullosa (CB) on lateral nasal wall asymmetries and septal deviation.